(untitled) (Journal of the College of Basic Education, 2022)
This study aimed at evaluating Almustansiriah University Faculty members, use of the internet in scientific research and recognizing the effect of academic title, sex and teaching experience on such use. The sample of study ,which was stratified and random ,consisted of 267 faculty members .the data were collected through a questionnaire that consisted of three domains : the rate of use , the degree of use and the diversity of use . the researcher used means, standard deviations , percentages , Manova, and pos-tests comparisons . the results of the study were : the rate of use was moderate and the degree of use was high ,there were statistically significant differences in the rate of use attributed to the variables of the study ,there were statistically significant differences in the degree of use attributed to the variables except sex ,and there was diversity in the use of the internet. Finally, the researchers concluded in this study by introducing a number of recommendations.